THE DIAGNOSIS STATUS OF RELAYS USING ARTIFICIAL NEURAL NETWORKS - Dub, V. Yu. (Science and Transport Progress, 2009)
In the paper the scientific substantiation of diagnostic method for the electromagnetic normal-acting DC relays by means of the neural networks is performed.